Insurance marketing development trends and peculiarities - Arych, Mykhailo (My University, 2019)
У роботі досліджено особливості розвитку страхового маркетингу в сучасних умовах. Вивчено та проаналізовано історію розвитку страхового маркетингу у двадцятому столітті та його сучасні особливості. Встановлено, що на вибір маркетингової стратегії страхової компанії впливають такі фактори, як цілі розвитку, умови діяльності, законодавче регулювання тощо. In this work the features of development of insurance marketing in modern conditions are investigated. The history of development of insurance marketing in the twentieth century and its modern features were studied and analyzed. It is established that the choice of marketing strategy of an insurance company is influenced by factors such as development goals, conditions of activity, legislative regulation, etc.
Keywords: insurance market; marketing; insurance marketing; insurance development; страховий ринок; маркетинг; страховий маркетинг; розвиток страхування; кафедра фінансів